ACCURACY OF ENTERAL SYRINGES FOR LIQUID MEDICINES PRESCRIBED IN CHILDREN. Issue 8 (11th July 2014) - Gurung, K; Arenas-Lopez, S; Wei, L; Tuleu, C
Abstract : Aim: To investigate the accuracy of two main brands available in UK hospitals of enteral syringes of different sizes, in delivering a range of clinically relevant volumes of commonly prescribed paediatric liquids.1 Method: Prospective in vitro study looked at volumes measured (0.05, 0.1, 0.2, 0.25, 0.5, 1, 2, 3 and 5 ml) 10 times with each single syringe size (1, 2.5/3 and 5 ml) and brand (Baxa and Medicina) as well as dead spaces. The weight of syringes, empty, filled and after expelling liquids were accurately weighed then converted into volume with the respective liquid densities. Sytron, Lanoxin-PG, One-alpha, Nifedipine Ratiopharm, Neoral, Amoxicillin 125 mg/5 ml SF, Calcium Carbonate, Ciproxin 250 mg/5 ml, Peppermint water BP 1973, Epanutin and water (control) were also characterized in terms of pH, conductivity, viscosity and surface tension (n=3). Appropriate statistics were applied to compare syringe brands (similar volumes), same volumes delivered with different size syringes and to explore any influence of the liquids characteristics (significance level: p<0.05). Results: Irrespectively of syringe size, volume and liquid delivered, the dead space was fairly constant for Baxa [0.07+/−0.05 ml] and for Medicina (wider tip) [0.13+/−0.08 ml]. Any volumes below or equal to 0.2 ml displayed larger variability, with some measured volumes outside a 90–110% of the intended volume range. Baxa delivered generally more than Medicina and than the intended volume. Comparison of accuracy of same volumes measured in different syringe sizes per brand was made. It highlighted some significant differences for most of the liquids showing that syringes sizes were not interchangeable, irrespectively of the brand. There were no correlation between the pharmaceutical characteristics and the accuracy of volume measurement apart from an unclear negative correlation between pH and 0.05 ml measured with syringe size of 1 ml. Full data analysis in final presentation. Conclusion: Dosing accuracy with enteral syringes commonly found in the HealthCare system was heterogenous for different brands, sizes and liquid characteristics especially for small volumes (0.25 ml and less) which are not uncommon volumes in paediatrics with the chosen drug in the present study. To improve safe medication in paediatric practice, carers should choose the right syringe (1 ml syringes only for small volumes) or round the dose volumes to the next accurate volume if the drug's therapeutic index permits, while manufacturers should be encouraged to consider carefully minimum dosing volumes for the youngest patients in relation to the strength of the product and recommend which administration devices to use based on assessment during pharmaceutical development.